(NpITANNQ L)QÆTERATUROZNAWSTWA (B:s)E (NNAUK(B. (NZB(B.s (NwIP(B. 72 /s - )Qæ(NN(B-(NT L(B-(NRI ÆM(B. (Nt(B. (Ng(B. (N{EW^ENKA nan uKRAÇNIs)E; (N~ERN)QÆW(B. (NNAC(B. (NUN(B-(NT ÆM(B. (N`RÆQ fEDXKOWI^As)E ((N~ERN)QÆWCÆ (B:s)E [(NB(B. (NW(B.] ;s, 2006)
(NwIPUSK M)QÆSTITX ZAGALXNOTEORETI^NÆ TA ÆSTORIKO(B-(NLÆTERATURNÆ STATTÆ(B, (NROZPODÆLENÆ ZA RUBRIKAMI (B"(NpOETIKA(B", "(NlÆTERATUROZNAW^A ÆSTORÆOGRAFÆQ(B", "(NgERMENEWTIKA(B", "(NrECEPCÆQ(B", "æ(NNTERPRETACÆQ(B", "(NmETODOLOGÆQ(B". (NpORU[ENÆ W STATTQH PITANNQ ROZGLQDA@TXSQ NA UKRAÇNSXKOMU(B, (NROSÆJSXKOMU(B, (NANGLOMOWNOMU(B, (NNÆMECXKOMOWNOMU TA FRANKOMOWNOMU MATERÆALÆ(B.s)E
Keywords: (Nl)QÆTERATUROZNAWSTWOs)E -- (NzB)QÆRNIKI(B.s)E